Moby.Cockpit Project for EV seamless integration in the cooperative transport infrastructure - Ferreira, João C. (2013)
Electric Vehicles (EV) are being introduced in the market, however the reduced energy storage capacity of their batteries and the lack of a high density charging infrastructure, limits their autonomy range. In order to overcome this limitation, we propose the development of a new solution for EV drivers that enables to travel longer distances. This is achieved by integrating some components of the cooperative transport infrastructure, as EV battery charging systems and public transports systems, and by increasing the driving autonomy through energy consumption reduction, achieved by driving efficiency increase. The integration with the charging infrastructure allows planning the journey of the driver, considering the position of charging points, and booking a charging point for a specific time period in order to perform the battery charging. Therefore, the distance that the driver can drive comfortably, without fearing running out of battery, is increased. The integration of the EV with public transports systems allows extending the travel distance beyond the EV drive autonomy, given by the storing capacity of vehicle’s battery. The supplying of information on availability, schedule and price of public transports allows planning the journey of the driver, using the EV and public transportation in a complementary way, through functions like car parking booking (and charging) and ticket buying.